Factors influencing Indonesian students' choice of studying at the International Islamic University Malaysia (IIUM) - Riswani Shamsuddin (International Islamic University Malaysia, 1998)
The purpose of this study is to investigate the factors influencing Indonesian students' choice of studying at the IIUM. It also attemps to identify whether there is any discernible pattern of reported factors between the male and female Indonesian undergraduate students. In addition, the pattern of responses toward the factors amongst students of different academic performances in examined. The score of this study consisted of 115 students who are studying at the IIUM. A self-constructed instrument was used for data collection and descriptive statistics were applied in the data analysis. The instrument comprises 33 items suggesting factors that influence students to study at the IIUM, Four categories of factors were included in the questionnaire: academic, personal, educational facilities and, social development and conteextual factors. The study found that the Indonesians study at the IIUM because they have a chance to meet other international Muslim brothers and sisters. Besides, they were free to enjoy the facilities, achieve their career preferences, experience new educational environment, the university activities and the Islamization of knowleldge as well as its pre-sessional courses in English and Arabic. The study also found that there is a discernible pattern of reported reasons between the male and female students as well as between the high performance students and the low performance students.